ANALISIS IMPLEMENTASI NILAI KARAKTER RELIGIUS, JUJUR, DAN TOLERANSI SISWA KELAS VI DI SD NEGERI 22 PALU - Sudarsana, Wayan; Yudani, Ni Kadek; Swanderi, Ketut; Ferensia, Ni Luh Selvi (JATMIKA : Journal Education and Learning of Elementary School, 2024)
This study aims to identify and analyze the implementation of character education values ​​in the daily activities of students at SD Negeri 22 Palu. This research is expected to be a reference in the development and implementation of character education in elementary schools and the community. The type of research used is a quantitative method with a descriptive approach. Data collection techniques using interviews and questionnaires. The data obtained from the questionnaire is then processed into quantitative data by giving each answer a weight. Respondents from this study were grade VI students at SD Negeri 22 Palu. This study, it focuses more on 3 indicators of character education values, namely religious values, honesty, and tolerance. Based on the results of processed descriptive data from 26 respondents who answered the questionnaire, it was found that the implementation of character values ​​with very good, good, and sufficient criteria had a total percentage of 81%. Meanwhile, only 19% included those with fewer criteria. So it can be concluded that the implementation of the three character values ​​is good even though not completely because there are still students who are lacking in implementing the intended character values.